The response of labour taxation to changes in government debt - Fédéric Holm-Hadulla; Nadine Leiner-Killinger; Michal Slavík (European Central Bank (ECB), 2011)
This paper investigates the relationship between government debt and labour taxation for a panel of 18 EU countries over the period 1979-2008. The econometric estimates point to a statistically significant and economically relevant positive response of labour taxation to changes in the general government debt and interest expenditure-to-GDP ratios. The results are robust across a range of econometric specifications and labour tax indicators.
Keywords: H2; H24; H63; J22; 330; debt; fiscal adjustment; labour taxes